2020
DOI: 10.1155/2020/8861251
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells in the Treatment of Neuropathic Pain: Research Progress of Mechanism

Abstract: Neuropathic pain (NP) is pain caused by somatosensory nervous system injury or disease. Its prominent symptoms are spontaneous pain, hyperalgesia, and allodynia, and the sense of pain is extremely strong. Owing to the complex mechanism, conventional painkillers lack effectiveness. Recently, research on the treatment of NP by stem cells is increasing and promising results have been achieved in preclinical research. In this review, we briefly introduce the neuropathic pain, the current treatment strategy, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 101 publications
0
26
0
Order By: Relevance
“…Given the low survival rate of the transplanted NPCs in our experiment as well as in comparable studies, their observed neuroprotective and neuroregenerative properties, even in such small quantities, are indeed remarkable [ 20 , 30 , 33 , 47 , 61 ]. While not assessed in our current experiment, it is noteworthy that transplanted NPCs have been associated with a reduction of neuropathic pain after SCI in animal models as well, possibly mediated by paracrine release of anti-inflammatory cytokines or the general attenuation of the cellular inflammatory response [ 70 , 71 ]. Future studies, therefore, should focus on synergistic treatment approaches, combining NPC-transplantation with, e.g., neuroprotective agents or interventions to increase survival and differentiation of the engrafted NPCs, which might considerably increase their neuroregenerative potential.…”
Section: Discussionmentioning
confidence: 99%
“…Given the low survival rate of the transplanted NPCs in our experiment as well as in comparable studies, their observed neuroprotective and neuroregenerative properties, even in such small quantities, are indeed remarkable [ 20 , 30 , 33 , 47 , 61 ]. While not assessed in our current experiment, it is noteworthy that transplanted NPCs have been associated with a reduction of neuropathic pain after SCI in animal models as well, possibly mediated by paracrine release of anti-inflammatory cytokines or the general attenuation of the cellular inflammatory response [ 70 , 71 ]. Future studies, therefore, should focus on synergistic treatment approaches, combining NPC-transplantation with, e.g., neuroprotective agents or interventions to increase survival and differentiation of the engrafted NPCs, which might considerably increase their neuroregenerative potential.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, damaged axons have been reported to secrete factors that activate the extracellular signal-related MAPK signal pathway in Schwann cells, which is crucial for inflammatory regulation ( Figure 3 ) [ 86 ]. There are four major MAPK-related pathways, namely, the ERK1/2, JNK, p38, and ERK5 cascades.…”
Section: Stem Cell Therapymentioning
confidence: 99%
“…This section does not include recent, more experimental approaches of neuropathic pain therapy. Hence, we would like to refer the reader to other reviews, for example, discussing stem cell technologies (Liu et al., 2020), electrical stimulation of peripheral nerves (Nayak & Banik, 2018), the spinal cord (Dones & Levi, 2018), or selected areas of the brain (Farrell et al., 2018) and the application of immunoglobulin (Chang & Park, 2020).…”
Section: Therapeutic Approachesmentioning
confidence: 99%